1993
DOI: 10.1001/archsurg.1993.01420140083013
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Autotransfusion in Hepatic Resection for Malignancy

Abstract: To evaluate whether intraoperative autologous transfusion increases the risk of hematogenous dissemination of tumor we reviewed the risk of lung metastasis as well as disease-free and long-term survival of patients who underwent resection of malignant hepatic neoplasms with this technique. A retrospective review of patients undergoing liver resection for malignant disease revealed 39 patients in whom intraoperative autologous transfusion was used. The 2-year actuarial survival in the patients in this series, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 21 publications
1
38
0
1
Order By: Relevance
“…All the in-vivo evidence has shown that cancer patients receiving cell salvaged blood do not get increased rates of recurrences or increased mortality, and there has been considerable clinical use of cell salvage in all types of cancer surgeryparticularly urology, over the last 20 years. Up to 2003 the evidence consisted of a small number of case reports and observational studies [51][52][53][54][55][56][57][58][59], and has been criticised as a result [50]. However, they do show no difference in recurrence rate with intra-operative cell salvage or a better outcome compared with allogeneic transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…All the in-vivo evidence has shown that cancer patients receiving cell salvaged blood do not get increased rates of recurrences or increased mortality, and there has been considerable clinical use of cell salvage in all types of cancer surgeryparticularly urology, over the last 20 years. Up to 2003 the evidence consisted of a small number of case reports and observational studies [51][52][53][54][55][56][57][58][59], and has been criticised as a result [50]. However, they do show no difference in recurrence rate with intra-operative cell salvage or a better outcome compared with allogeneic transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh frozen plasma was used in patients with Child-Pugh grade B disease. None of the patients received intraoperative haemodilution 11 , intraoperative blood salvage 12 or autologous blood transfusion 13 -15 .…”
Section: Methodsmentioning
confidence: 99%
“…64 Malignancy recurrence or metastases secondary to perioperative transfusion practices is a difficult field of study given the heterogeneity of the clinical circumstance, the type and stage of cancer, and the long follow-up times required. Nonetheless, 15 clinical studies have been published reporting outcomes on patients who received transfusion of ICS blood intraoperatively during malignancy surgery [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] (Table 3). The majority of these studies were single-centre non-randomized small studies where the outcome of patients who received intraoperative ICS blood was compared with historic or case controls.…”
Section: Clinical Experiencementioning
confidence: 99%